(untitled) (Research, Society and Development, 2023)
In Brazil, there is a great cultural and social diversity, which leads to the use of several natural products due to their ethnopharmacological properties, incluing honey. Honey is a nutrient-rich food that has several beneficial activities, such as: anti-inflammatory, antioxidant, antimicrobial and nematicidal actions. However, there are no studies regarding the nematicidal effect of honeys from Brazil. Thus, the objective of this study was to evaluate the nematicidal action of honeys of Apis mellifera L. from orange, avocado, eucalyptus, multifloral and honey from Tetragonisca angustula species (known as Jataí) on Panagrellus sp. nematodes. In the nematicidal assays, solutions of these honeys were used in concentrations of 3; 1.5; 0.75 and 0.5% (w/v). The control group contained only distilled water. In assays with a concentration of 0.5% of avocado honey and T. angustula bee honey, a significant reduction was demonstrated, compared to the control group (respectively: 41.4% and 47.2%). The results obtained demonstrated, for the first time, that A. mellifera L. honey from avocado flowering and T. angustula honey showed significant nematicidal activity against juveniles of the free-living nematode model Panagrellus sp. Therefore, further studies on the compositions of these honeys must be developed.